Diversity analysis of mangosteen (Garcinia mangostana) irradiated by gamma-ray based on morphological and anatomical characteristics - ALFIN WIDIASTUTI; SOBIR SOBIR; MUH RAHMAD SUHARTANTO (Nusantara Bioscience, 2010)
Abstract. Widiastuti A, Sobir, Suhartanto MR. 2010. Diversity analysis of mangosteen (Garcinia mangostana L.) irradiated by gamma-ray based on morphological and anatomical characteristics. Nusantara Bioscience 2: 23-33. The aim of this research was to increase genetic variability of mangosteen (Garcinia mangostana L.) irradiated by gamma rays dosage of 0 Gy, 20 Gy, 25 Gy, 30 Gy,35 Gy, and 40 Gy. Plant materials used were seeds collected from Cengal Sub-village, Karancak Village, Leuwiliang Sub-district, Bogor District, West Java. Data was generated from morphological and anatomical characteristics. The result indicated that increasing gamma-ray dosage had inhibited ability of seed to grow, which needed longer time and decreased seed viability. Morphologically, it also decreased plant height, stem diameter, leaf seizure, and amount of leaf. Anatomically, stomatal density had positive correlation with plant height by correlation was 90% and 74%. Gamma rays irradiation successfully increase morphological variability until 30%. Seed cleavage after irradiation increased variability and survival rate of mangosteen.